(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Organizational performance is a key indicator of institutional success in dynamic and competitive environments, with digital transformation increasingly recognized as a critical driver of performance improvement. This study investigates the impact of digital transformation and its dimensions on organizational performance. Adopting a descriptive-analytical approach, data were collected through a questionnaire administered to a stratified random sample of 175 administrative employees from the Governor’s Office and its affiliated departments. The results reveal a statistically significant effect of digital transformation on organizational performance, with variation across its dimensions. While the technical and human dimensions showed significant positive effects, the organizational-cultural and strategic dimensions did not demonstrate significant impacts. Accordingly, the study recommends periodic evaluation of digital transformation initiatives, fostering an innovation-supportive organizational culture, and investing in digital and innovative projects to enhance organizational performance and ensure sustainable institutional effectiveness.